Excitability of the Ipsilateral Primary Motor Cortex During Unilateral Goal-Directed Movement - Matsumoto, Takuya; Watanabe, Tatsunori; Kuwabara, Takayuki; Yunoki, Keisuke; Chen, Xiaoxiao; Kubo, Nami; Kirimoto, Hikari (Frontiers in Human Neuroscience, 2021)
Introduction: Previous transcranial magnetic stimulation (TMS) studies have revealed that the activity of the primary motor cortex ipsilateral to an active hand (ipsi-M1) plays an important role in motor control. The aim of this study was to investigate whether the ipsi-M1 excitability would be influenced by goal-directed movement and laterality during unilateral finger movements. Method: Ten healthy right-handed subjects performed four finger tapping tasks with the index finger: 1) simple tapping (Tap) task, 2) Real-word task, 3) Pseudoword task, and 4) Visually-guided tapping (VT) task. In the Tap task, the subject performed self-paced simple tapping on a touch screen. In the Real-word task, the subject tapped letters displayed on the screen one by one to create a real-word (e.g., apple). Because the action had a specific purpose (i.e., creating a word), this task was considered to be goal-directed as compared to the Tap task. In the Pseudoword task, the subject tapped the letters to create a pseudoword (e.g., gdiok) in the same manner as in the Real-word task; however, the word was less meaningful. In the VT task, the subject was required to touch a series of illuminated buttons. This task was considered to be less goal-directed than the Pseudoword task. The tasks were performed with the right and left hand, and a rest condition was added as control. Single- and paired-pulse TMS were applied to the ipsi-M1 to measure corticospinal excitability and short- and long-interval intracortical inhibition (SICI and LICI) in the resting first dorsal interosseous muscle. Results: We found the smaller SICI in the ipsi-M1 during the VT task compared with the resting condition. Further, both SICI and LICI were smaller in the right than in the left M1, regardless of the task conditions. Discussion: We found that SICI in the ipsi-M1 is smaller during visual illumination-guided finger movement than during the resting condition. Our finding provides basic data for designing a rehabilitation program that modulates the M1 ipsilateral to the moving limb, for example, for post-stroke patients with severe hemiparesis.